Auricular acupoints sticking-pressing therapy in treating one case of gout and related nursing management (耳穴贴压治疗痛风1例护理体会) - WANG Chun (王纯); TANG Ling (唐玲); LI Ye (李野); ZHAO Lixue (赵丽雪); LI Suqian (李苏茜) (中西医结合护理)
This paper summarized the nursing measures for a case of gout treated by auricular acupoints sticking-pressing therapy. Key issues of nursing included living care, dietary instruction, psychological intervention, procedure and cautions of auricular acupoints sticking-pressing therapy. Based on the scientific evaluation and acupoints selection by syndrome differentiation, targeted nursing interventions are effective to reduce the pain and improve the quality of life in patients with gout. (本文总结了1例耳穴贴压治疗痛风的护理经验, 包括生活护理、饮食指导、心理干预以及耳穴贴压的操作方法和注意事项。通过科学的评估, 辨证取穴, 开展针对性护理干预, 有助于缓解患者痛风症状, 减轻疼痛, 改善日常生活能力。)